Wolf Hall : a novel - Mantel, Hilary, 1952- (New York : Henry Holt and Co., 2009)
Assuming the power recently lost by the disgraced Cardinal Wolsey, Thomas Cromwell counsels a mercurial Henry VIII on the latter's efforts to marry Anne Boleyn against the wishes of Rome, a successful endeavor that comes with a dangerous price. Employing a vast array of historical characters, and a story overflowing with incident, the author turns Tudor England into a compelling piece of fiction. Mantel re-creates an era when the personal and political are separated by a hairsbreadth, where success brings unlimited power but a single failure means death. -- from Book Jacket
Cast of characters -- Family trees -- Across the narrow sea, 1500 -- Paternity, 1527 -- At Austin Friars, 1527 -- Visitation, 1529 -- An occult history of Britain, 1521-1529 -- Make or mar, all hollows, 1529 -- Three-card trick, winter 1529-spring 1530 -- Entirely beloved Cromwell, spring-December 1530 -- The dead complain of their burial, Christmastide, 1530 -- Arrange your face, 1531 -- "Alas, What Shall I Do For Love?", spring 1532 -- Early mass, November, 1532 -- Anna Regina, 1533 -- Devil's spit, autumn and winter 1533 -- A painter's eye, 1534 -- Supremacy, 1534 -- The map of Christendom, 1534-1535 -- To Wolf Hall, July 1535 -- Author's note
"A John Macrae book."
Keywords: Cromwell, Thomas, -- Earl of Essex, -- 1485?-1540 -- Fiction; Fictional Works; Great Britain -- History -- Henry VIII, 1509-1547 -- Fiction; Historical fiction; Fiction